Rajmahal Hills Used in Diabetes Management - Mandal, Saroj Kumar; Soren, Rosline (American Journal of Botany and Bioengineering, 2025)
Medicinal plants possess an important therapeutic aid for alleviating ailments of humankind. Five such plants namely Moringa oleifera (MORINAGACEAE), Raphanus sativas (BRASSICACEAE), Murraya koenigii (RUTACEAE), Withania coagulans (SOLANACEAE) and Emblica officinalis (EUPHORBIACEAE) have been taken into account as aid in diabetes management. Actually diabetes mellitus is a serious metabolic disorder affecting about 20% of the world population. An increasing number of people are therefore, seeking alternative therapies from medicinal plants having minimal side effects.